(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
The incidence of HIV infection in the world is steadily increasing. The total number of people infected with HIV in 2022 reached 39 million people. Of these, 37.5 million are people aged 15 years and older, and 1.5 million are younger. The majority (53%) were female [Fact sheet - Global HIV statistics, UNAIDS]. The impact of HIV infection on the occurrence and progression of various obstetric complications is a subject of debate among most researchers. Some authors associate the development of gestational complications with the level of viral load, the state of the immune system, others with the duration of the infectious process, as well as the presence of concomitant coinfection or obstetric history.